The Medical Mission and Modern Core Competency Training: A 10-Year Follow-Up of Resident Experiences in Global Plastic Surgery. Issue 3 (September 2016) - Yao, Caroline A.; Swanson, Jordan; McCullough, Meghan; Taro, Trisa B.; Gutierrez, Ricardo; Bradshaw, Allison; Campbell, Alex; Magee, William P.; Magee, William P.
Abstract : Background: The emphasis on cultural competency for physicians and surgeons is increasingly important, as communication with both patients and other providers significantly affects individual and system-wide outcomes. International surgical training has been shown to improve leadership skills, cultural competency, and technical proficiency of participants in short-term follow-up. This study explores the long-term impact of international surgical mission experiences on developing participants' core competencies, professional outcomes, and commitment to global health. Methods: All 208 plastic and reconstructive surgeons who completed the Operation Smile Regan/Stryker fellowship programs between 2006 and 2015 were surveyed electronically. Results: One hundred sixty-five surveys were returned, for an overall response rate of 79.3 percent. The majority of participants reported that the fellowship positively impacted all six Accreditation Council for Graduate Medical Education core competencies. Most participants who were attending physicians at the time of the survey were practicing general plastic surgery, with 42 percent in an academic/teaching environment, 32 percent in assistant/associate professor positions, and 6 percent in either a program director or department chairman position. The majority currently volunteer on local or international missions, and all respondents would consider volunteering again. Conclusions: Carefully structured and rigorously proctored programs such as the Regan/Stryker Fellowship offer plastic surgery residents the opportunity to gain valuable professional and personal experiences that benefit them long after their service experience. Programs of this nature can not only effectively improve cultural competency of physicians, but also positively influence their attitudes toward leadership and direct that potential to meet the growing need for surgical care in low- and middle-income countries. Abstract : This and Related "Classic" Articles Appear on Prsjournal.Com for Journal Club Discussions.